Refleksi Pandemi Covid-19: Dampak Dan Peluang Membangun Peradaban Berbasis Solidaritas Global: Reflection Of Covid-19 Pandemic: The Impact And Opportunity Of Civilization Developing Based On Global Solidarity - Putra, Andreas Maurenis (Societas Dei: Jurnal Agama dan Masyarakat, 2021)
Even though the theme discussed in this paper is the Covid-19 pandemic, the real background is the world that behind the Covid-19 pandemic, namely, civilization which today has filled with fear, conspiracy, group interests, indifference and injustice. They are actually caused by the humans themselves. Based on this context, the author tries to show that the Covid-19 pandemic is not only a disaster but also an opportunity to lead for a new civilization of global solidarity in the world. Using the literature method (library research), this research was conducted by, first, reading the phenomenon about Covid-19 from the literature. Second, comparing it with central areas in life, and third, draws normative ethical implication which is global solidarity and theological implications in faith inspires a global solidarity movement, especially for Christians, rests on the cross and the resurrection. Keywords: Covid-19; Civilization; Normative-Ethical Implication; Theological Implication; Global Solidarity.